KEWENANGAN PELAKSANAAN EKSEKUSI OLEH KREDITUR TERHADAP JAMINAN FIDUSIA DALAM HAL DEBITUR WANPRESTASI - Widnyana, I Gede; Walesa Putra, I Made (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 02, Februari 2014, 2014)
This paper, entitled "Excuting Authority by Creditors Against Debtors Fiduciary Assignment in terms of Default". This paper uses the juridical normative analysis methods and approaches to legislation. The presence of Act Number 42 of 1999 regarding fiduciary Guarantee, is expected to create a strong security institution and is able to provide legal certainty for the borrower. However, in implementing, appeared a problem arising in the granting of loans with a guarantee that the debtor did not meet the fiduciary obligations of the debtor do or default. Therefore, this paper describes the implementation of execution by creditors against debtors in terms of fidusisia guarantee default.
Keywords: Execution, The Debtor, Fiduciary Assignment, Default